In vitro Evaluation of Newer Unconventional Feedstuffs for Livestock - Banakar, Praveen S.; Kulangara, Ally; Prasad, Chikkagoudara K.; Soren, Nira M.; Dominic, George; Terhuja, Megolhubino (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study assessed the chemical composition, digestibility, and fermentation metabolites of six unconventional feedstuffs: bamboo leaves (BL), turmeric waste (TW), spent cumin (SC), cooked barley residue (CBR), water hyacinth (WH), and soya sauce waste (SSW) as ruminant feedstuffs through in vitro gas production test. The crude protein content ranged from 11.82% (CBR) to 17.98% (WH), while the ether extract was higher in SSW, followed by TW. The neutral detergent fiber (NDF) content was lower in WH (46.6%) and higher in TW (65.83%), while the acid detergent fiber (ADF) was higher in TW and lowered in SSW. Spent cumin had higher lignin than turmeric waste. Gas production (mL/200 mg; 24 h) was higher (p <0.05) in CBR and lowest in the SSW sample. The digestibility of dry matter (DM) and organic matter (OM) followed the same pattern and were higher (p <0.05) in CBR and lower in the BL sample. The microbial biomass production (mg/200 mg DM) was significantly (p <0.05) higher in SSW and lower in CBR and BL samples. The ME (MJ/ kg DM) was higher (p <0.05) for CBR and lower for BL and SSW samples. The NH3-N (mg/100 mL) concentration was higher (p <0.05) in BL and SSW and lower in other samples. Acetate production was higher (p <0.05) in WH and lowest in other samples, while CBR and WH samples yielded more (p <0.05) propionate than other samples. Total short-chain fatty acids (SCFA) production was higher (p <0.05) in CBR and WH and lowest in other feed samples. Newer feedstuffs like cooked barley residue spent cumin and water hyacinth were highly digestible and rich in energy and therefore can be fed to ruminants.